The Latin American and Caribbean digital divide: a geospatial and multivariate analysis. Issue 2 (3rd April 2021) - Pick, James; Sarkar, Avijit; Parrish, Elizabeth
ABSTRACT: This paper examines spatial patterns of information and communication technology (ICT) adoption and utilization and seeks to understand underlying reasons for the digital divide in Latin America and the Caribbean (LAC). Five distinctive clusters of technology adoption and use factors are identified, characterized, and geographically mapped. Disparities in adoption and utilization in ICTs in 36 LAC countries are examined Using a Spatially Aware Technology Utilization Model, fifteen socioeconomic, innovation, business efficiency, infrastructural, affordability, and societal openness indicators are posited to be associated with six ICT indicators. Human development, civil liberties, political rights, urban population, and electricity access are found to influence ICT adoption and use in LAC indicating socio-economic, urban, societal openness, and infrastructural dimensions of the digital divide in this world region. For a sub-sample of Latin American nations, regression findings point to human development and infrastructural factors. Spatial bias in confirmatory analysis is diagnosed, and policies are recommended.